ANTIMICROBIAL ACTIVITY OF VARIOUS PLANTS EXTRACTSAGAINST SOME COMMON PATHOGENIC MICROORGANISM - Waleed, Sinai (Al-Nahrain Journal of Science, 2018)
The effects of plants aqueous extracts (Myrtle, Harmal, Henna, Thyme and Fenugreek) against some clinical species of microorganisms were studied. These isolates included: Pseudomonas sp., Klebseilla sp., Escherichia coli, Proteus sp., Staphylococcus aureus and Candida albicans. The susceptibility of these isolates was tested against plants aqueous extracts by the agar well diffusion method. The results showed that the aqueous extract of Myrtle inhibited the growth of all tested microorganisms at concentration 5%, followed by Harmal when all tested bacteria were inhibited at concentration 10% except C. albicans inhibited at 20%. Compare with Henna when all bacteria were inhibited at concentration 20% except C. albicans was resistant, followed by Thyme which only two bacteria (Klebsiella sp. & Staphylococcus aureus) were inhibited at 20% while the remaining microorganism were resistant. On other hand all tested microorganisms were resistant to Fenugreek even at high concentration.